Penerapan Pendekatan TaRL dengan Model PBL untuk Meningkatkan Hasil Belajar Matematika Peserta Didik - Pratiwi, Anggraini; Sembiring, Metrilitna Br; Pradesa, Dedi (Education Journal : Journal Educational Research and Development, 2024)
This Classroom Action Research (CAR) aims to improve the mathematics learning outcomes of class XI Biosfer students from SMA Negeri 2 Medan through the application of the Teaching at the Right Level (TaRL) approach using the Problem Based Learning (PBL) model on polynomial materials. The research consists of pre-cycle, cycle I, and cycle II. Each cycle consists of several stages, namely, planning, implementation, observation, evaluation, and reflection, which are conducted on 36 class XI Biosfer students in the 2024/2025 academic year. The TaRL approach with the PBL learning model was applied during Cycles I and II, each consisting of two meetings. Data collection at the pre-cycle stage was carried out through cognitive diagnostic assessments and interviews with mathematics teachers. In Cycles I and II, measurements are carried out through cognitive tests at the end of each cycle. The results of the study showed a significant increase in the average value and percentage of learning outcome completion. In the pre-cycle stage, the average value and percentage of completion were 60 (36.1%), which then increased in cycle I to 72.5 (61.1%) and further increased in cycle II to 86.1 (80.5%). This finding confirms that the application of the TaRL approach with the PBL learning model can effectively improve mathematics learning outcomes in students. The results of this study can be used as a reference for teachers, schools, and other researchers seeking to improve the effectiveness of classroom learning.